A novel chemically modified curcumin reduces inflammation‐mediated connective tissue breakdown in a rat model of diabetes: periodontal and systemic effects. (1st April 2016) - Elburki, M. S.; Moore, D. D.; Terezakis, N. G.; Zhang, Y.; Lee, H.‐M.; Johnson, F.; Golub, L. M.
Abstract : Background and Objective: Periodontal disease is the most common chronic inflammatory disease known to mankind (and the major cause of tooth loss in the adult population) and has also been linked to various systemic diseases, particularly diabetes mellitus. Based on the literature linking periodontal disease with diabetes in a "bidirectional manner", the objectives of the current study were to determine: (i) the effect of a model of periodontitis, complicated by diabetes, on mechanisms of tissue breakdown including bone loss; and (ii) the response of the combination of this local and systemic phenotype to a novel pleiotropic matrix metalloproteinase inhibitor, chemically modified curcumin (CMC) 2.24. Material and Methods: Diabetes was induced in adult male rats by intravenous injection of streptozotocin (nondiabetic rats served as controls), and Escherichia coli endotoxin (lipopolysaccharide) was repeatedly injected into the gingiva to induce periodontitis. CMC 2.24 was administered by oral gavage (30 mg/kg) daily; untreated diabetic rats received vehicle alone. After 3 wk of treatment, the rats were killed, and gingiva, jaws, tibia and skin were collected. The maxillary jaws and tibia were dissected and radiographed. The gingival tissues of each experimental group ( n = 6 rats/group) were pooled, extracted, partially purified and, together with individual skin samples, analyzed for matrix metalloproteinase (MMP)‐2 and MMP‐9 by gelatin zymography; MMP‐8 was analyzed in gingival and skin tissue extracts, and in serum, by western blotting. The levels of three bone‐resorptive cytokines [interleukin (IL)‐1β, IL‐6 and tumor necrosis factor‐α], were measured in gingival tissue extracts and serum by ELISA. Results: Systemic administration of CMC 2.24 to diabetic rats with endotoxin‐induced periodontitis significantly inhibited alveolar bone loss and attenuated the severity of local and systemic inflammation. Moreover, this novel tri‐ketonic phenylaminocarbonyl curcumin (CMC 2.24) appeared to reduce the pathologically excessive levels of inducible MMPs to near‐normal levels, but appeared to have no significant effect on the constitutive MMPs required for physiologic connective tissue turnover. In addition to the beneficial effects on periodontal disease, induced both locally and systemically, CMC 2.24 also favorably affected extra‐oral connective tissues, skin and skeletal bone. Conclusion: This study supports our hypothesis that CMC 2.24 is a potential therapeutic pleiotropic MMP inhibitor, with both intracellular and extracellular effects, which reduces local and systemic inflammation and prevents hyperglycemia‐ and bacteria‐induced connective tissue destruction.